Efektivitas Strategi Index Card Match (ICM) Pada embelajaran IPS Materi Proses Pembentukan Perilaku Menyimpang Siswa Kelas VIII SMP Negeri 2 Banyudono Tahun Pelajaran 2014/2015 - Suhandoko, Suhandoko; , Drs. Dahroni, M.Si (2015)
This study was motivated by the implementation of learning that is still slightly involving students. The purpose of this study was to determine the influence of Index Card Match strategy towards the understanding of social studies lesson on the material forming process deviant behavior. This study uses the method of documentation and test where the instrument has been tested, tested the validity and reliability testing. Data analysis technique used is the prerequisite test and test hypotheses. Results of research on the normality test of the experimental class and control class gained significant> 0.05 meaning that the data are normally distributed. Homogeneity test results obtained pretest both classes singnifikan> 0.05 meaning that the data has the same variance homogeneity test results while the post-test <0.05 means that the data have not the same variance. Sample Test Results Paired t-test was significantly gained 0,002 and 0,000 related real meaning. Independent test results Sample t-test was significantly obtained 0.001 <0.05 means that H0 is rejected. Results of data analysis known that there is an increasing understanding of social studies on the material after the process of formation of deviant behavior strategy applied Index Card Match. It can be shown in two different test results on average, in classes that are applied strategy Index Card Match obtained the average value of 66.68 and conventional learning obtained an average value of 63.03 means that the use of learning strategies Index Card Match student achievement more both compared with conventional learning. Strategy Index Card Match in an effort to improve student understanding and the results of student achievement that needs to be supported by all parties.